2015
DOI: 10.1080/02705060.2015.1015058
|View full text |Cite
|
Sign up to set email alerts
|

The effects of severe flooding on native masu salmon and nonnative rainbow trout in the Atsuta River, Hokkaido, Japan

Abstract: Debris flow has potentially pronounced effects on streams and fish populations. In August 2010, a severe flood, which was coupled with wide-ranging landslides and massive debris flows, occurred in the Atsuta River. In this study, we evaluated the effects of floods on salmonid populations by examining the abundance and density of masu salmon Oncorhynchus masou and rainbow trout O. mykiss in the Atsuta River and comparing these values in the post-flood period to those in the pre-flood period. The estimated abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These flows in 2013 substantially restructured fish habitat throughout the LBR (City of Calgary 2018). Previous studies that have assessed the impact of severe flood events on trout abundances have found responses ranging from dramatic decreases in trout density (Jowett and Richardson 1989;Kitanishi and Yamamoto 2015) to no change between pre-and postflood measurement periods (George et al 2015). High flow events leading to food supply limitations and subsequent population collapse were responsible for boom-and-bust population cycles in a tailwater rainbow trout fishery below the Glen Canyon Dam in Arizona (Korman et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These flows in 2013 substantially restructured fish habitat throughout the LBR (City of Calgary 2018). Previous studies that have assessed the impact of severe flood events on trout abundances have found responses ranging from dramatic decreases in trout density (Jowett and Richardson 1989;Kitanishi and Yamamoto 2015) to no change between pre-and postflood measurement periods (George et al 2015). High flow events leading to food supply limitations and subsequent population collapse were responsible for boom-and-bust population cycles in a tailwater rainbow trout fishery below the Glen Canyon Dam in Arizona (Korman et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Palstra & Ruzzante, ). It is possible that the effects of demographic or environmental stochasticity on genetic characteristics may be hidden over the longer term due to re‐establishing or recovering populations from neighbouring sites and consistent gene flow (Kitanishi & Yamamoto, ; Palstra & Ruzzante, ). Overall, these factors combined with the local life‐history variations such as density and age structure may generate a wide variety of temporal genetic structures among species or populations.…”
Section: Discussionmentioning
confidence: 99%
“…Palstra & Ruzzante, 2010). It is possible that the effects of demographic or environmental stochasticity on genetic characteristics may be hidden over the longer term due to re-establishing or recovering populations from neighbouring sites and consistent gene flow (Kitanishi & Yamamoto, 2015b;Palstra & Ruzzante, 2010). Overall, these factors combined with the local life-history variations such as density and age structure may gener- Previous studies documented that masu salmon showed fine-scale genetic structure that indicate relatively stable population structure (Kitanishi et al, 2009), and suggested that precise homing and low reproductive success of dispersers contribute to the stability of genetic structuring in masu salmon (Kitanishi & Yamamoto, 2015a;Kitanishi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%